2021
DOI: 10.48550/arxiv.2109.03023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cooper-Pair Box Coupled to Two Resonators: An Architecture for a Quantum Refrigerator

Andrew Guthrie,
Christoforus Dimas Satrya,
Yu-Cheng Chang
et al.

Abstract: Here we present an architecture for the implementation of cyclic quantum thermal engines using a superconducting circuit. The quantum engine consists of a gated Cooper-pair box, capacitively coupled to two superconducting coplanar waveguide resonators with different frequencies, acting as thermal baths. We experimentally demonstrate the strong coupling of a charge qubit to two superconducting resonators, with the ability to perform voltage driving of the qubit at GHz frequencies. By terminating the resonators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…These estimates are very encouraging for the experimental implementation of this machine. In this sense, a very promising platform is a superconducting qubit coupled to resonators, in which there are several configurations under study for some years now [67][68][69][70][71][72]. Other possible platforms are those in which the Otto cycle has been already implemented, like AMO systems [2,73,74], as well as spin systems in NMR setups [6].…”
Section: Discussionmentioning
confidence: 99%
“…These estimates are very encouraging for the experimental implementation of this machine. In this sense, a very promising platform is a superconducting qubit coupled to resonators, in which there are several configurations under study for some years now [67][68][69][70][71][72]. Other possible platforms are those in which the Otto cycle has been already implemented, like AMO systems [2,73,74], as well as spin systems in NMR setups [6].…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al 377 then demonstrated, theoretically as well as experimentally, that the spin-qubit device can operate as both, engine as well as refrigerator, in the classical and in the fully quantum coherent regime. Despite its rather recent publication, this study has already inspired follow-up work in the design of heat engines 338,385 and in the observation of the spin blockade 386 .…”
Section: Silicon Tunnel Field-effect Transistormentioning
confidence: 99%
“…Indeed, it is difficult to imagine a "quantum society" where computing, communications, and sensing will be carried out by relying on the principles of quantum mechanical laws while energy will be provided by systems ruled by standard electrochemical laws and 200-years old designs. There are three classes of energy-related quantum devices, which are currently being mainly studied by academia and that will need to gradually be evaluated and adopted by industry: i) quantum heat engines for energy production [187][188][189][190][191][192][193][194], ii) quantum batteries [195][196][197][198][199][200][201][202][203][204][205] and supercapacitors [206] for energy storage, and iii) quantum energy lines [207] for energy transfer. Research and development on all these aspects may lead to a profound "cultural" and technological revolution in how energy is produced, stored, and conveyed.…”
Section: Quantum Technologies For the Energy Sectormentioning
confidence: 99%